Exposure to per- and polyfluoroalkyl substances is associated with impaired cardiovascular health: a cross-sectional study - Zong, Shuli; Wang, Lin; Wang, Sutong; Wang, Yongcheng; Jiang, Yuehua; Sun, Liping; Zong, Yingying; Li, Xiao (Frontiers in Public Health, 2024)
Background Per- and polyfluoroalkyl substance (PFAS) exposure and cardiovascular disease are controversial. We aimed to assess the association between serum PFAS exposure and cardiovascular health (CVH) in U.S. adults. Methods We analyzed serum PFAS concentration data of U.S. adults reported in the National Health and Nutrition Examination Survey (NHANES) study (2005–2018). We employed two weighted logistic regression models and a restricted cubic spline (RCS) to examine the association between each PFAS and impaired CVH (defined as moderate and low CVH). Quantile g-computation (Qgcomp) and weighted quantile sum (WQS) analysis were used to estimate the effects of mixed exposures to PFASs on impaired CVH. Results PFAS were associated with an increased risk of impaired CVH (ORPFNA: 1.40, 95% CI: 1.09, 1.80; ORPFOA: 1.44, 95% CI: 1.10, 1.88; ORPFOS: 1.62, 95% CI: 1.25, 2.11). PFOA and PFOS exhibited nonlinear relationships with impaired CVH. Significant interactions were observed for impaired CVH between race/ethnicity and PFHxS (p = 0.02), marital status and PFOA (p = 0.03), and both marital status and race/ethnicity with PFOS (p = 0.01 and p = 0.02, respectively). Analysis via WQS and Qgcomp revealed that the mixture of PFAS was positively associated with an increased risk of impaired CVH. Conclusion PFNA, PFOA, and PFOS exposure are associated with an increased risk of impaired CVH in U.S. adults. Race/ethnicity and marital status may influence CVH. Reducing PFAS exposure could alleviate the burden of disease associated with impaired CVH.